Sistem Pendukung Keputusan Pemilihan Paket Makanan Dengan Metode Analytical Hierarchy Process (Ahp) Dan Simple Additive Weighting (Saw) Pada Catering Bu Sri - Kusuma, Novianto Indra; Lemantara, Julianto; Tjandrarini, A. B. (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2021)
Currently, the competition in the catering industry is very competitive. This is indicated by the increasing number of catering industries. Catering Bu Sri is a home catering business that serves orders for boxed rice and tumpeng for various events. Catering Bu Sri provides a varied food menu, including 5 kinds of rice, 20 main side dishes, and 13 side dishes. The problem that is often faced by customers and Catering Bu Sri is, customers are confused about choosing food menu to order into one menu package, the catering staff must choose the food menu according to customer criteria, and the time needed to select or recommend a food package according to the criteria is quite long, is about 15-30 minutes. The solution based on these problems is by making a decision support system for selecting food packages using the Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) method. The process carried out is by filtering the data based on the criteria for the number of menus and the level of vegetarianism, then combined to become a food package. Combination results will be filtered based on 75% to 100% of the customer's budget. Analytical Hierarchy Process method will be used to determine the priority weights for each criterion, and Simple Additive Weighting method will be used to determine global priority by multiplying the value of all alternatives on all criteria by the average value of the criteria. Based on the test, the system that has been created can help customers and the catering party in selecting or recommending food packages according to the criteria and speeding up the time for selecting food packages by 60 to 90 times from the previous process.